PERAN AGAMA DALAM PEMBERDAYAAN INTEGRASI NASIONAL - Ismail, Farhan Muhammad; Ediyono, Suryo (PKn Progresif : Jurnal Pemikiran dan Penelitian Kewarganegaraan, 2023)
ABSTRACTThis study aims to determine the extent to which religion plays a role in maintaining the integrity of the nation and as a solution to various structural and horizontal conflicts in various regions of Indonesia which are caused, among other things, by the application of religious emotional content. transgressed, as did the glorification of tribes and ethnicities that grew. The challenge that we must face together is to consciously and honestly shape the role of religious, moral and ethnic values to promote harmony, unity, social cohesion, national integration and national resilience in the era of globalization. Partnerships between nations and countries must be encouraged in order to promote regional sustainability, because realizing national and regional sustainability seeks to realize the ideals of the nation as contained in the preamble of the 1945 Constitution.Keywords: Indonesia, Moral, Nation, National, Tribe, Ethnicity  ABSTRAKKajian ini bertujuan untuk mengetahui sejauh mana agama berperan dalam menjaga keutuhan bangsa dan sebagai solusi atas berbagai konflik struktural dan horizontal di berbagai wilaya h Indonesia yang antara lain disebabkan oleh penerapan muatan emosional keagamaan. melampaui batas, seperti halnya pemuliaan suku dan etnis yang tumbuh. Tantangan yang harus kita hadapi bersama adalah secara sadar dan jujur membentuk peran nilai-nilai agama, moral, dan etnis untuk mendorong kerukunan, persatuan, kohesi sosial, integrasi bangsa, dan ketahanan nasional di era globalisasi. Kemitraan antar bangsa dan negara harus digalakka n dalam rangka memajukan kesinambungan daerah, karena mewujudkan kesinambunga n nasional dan daerah berupaya mewujudkan cita-cita bangsa yang tertuang dalam pembukaan UUD 1945.Kata kunci : Indonesia, Moral, Bangsa, Nasional, Suku, Etnik